Math, asked by Anonymous, 5 months ago

Solve:-


Spam Answer will be reported.​

Attachments:

Answers

Answered by Anonymous
65

\huge\underline{\overline{\mid{\bold{\blue{\mathcal{ANSWER}}\mid}}}}

Given:-

 \frac{cos  A   -  sin  A  +   1}{cos  A  + sin  A  - 1}  = cosec  A  + cot A

L.H.S = \frac{cos  A   -  sin  A  +   1}{cos  A  + sin  A  - 1}

R.H.S = cosec  A  + cot A

To Prove:-

 \frac{cos  A   -  sin  A  +   1}{cos  A  + sin  A  - 1}  = cosec  A  + cot A

Proof:-

Let us Solve the L.H.S to solve this

L.H.S = \frac{cos  A   -  sin  A  +   1}{cos  A  + sin  A  - 1}

Divide Numerator and Denominator by Sin A

 =  >  \frac{ \frac{cos  A   -  sin  A  +   1}{sin \: A} }{ \frac{cos  A    +  sin  A   -   1}{sin  A  } }

 =  >  \frac{ \frac{cos A  }{sin  A  } -  \frac{sin  A  }{sin  A  }  +   \frac{1}{sin  A  }   }{ \frac{cos A  }{sin  A  }  +  \frac{sin  A  }{sin  A  } -  \frac{1}{sin  A  }  }

Now, we will use Trigonometric ratios

 =  >  \frac{cot A    - 1 +cosecA  }{cot A     +  1  - cosecA}

We can write :

 1 =  {cosec}^{2} A   +  {cot}^{2} A

as this is a Trigonometry identity

So,

 =  >  \frac{cot A   + cosecA - ( {cosec}^{2}A -  {cot}^{2}A)}{cot A      + 1    -  cosecA}

 =  >  \frac{cot A   + cosecA - ( cosecA -  cotA)(cosecA -  cotA)}{cot A      + 1    -  cosecA}

 =  >  \frac{(cot A   + cosecA )( 1   -  cosecA  +  cotA)}{cot A      + 1    -  cosecA}

 =  > cot A   + cosecA

L.H.S = cot A   + cosecA

Now,

L.H.S=R.H.S

HENCE , PROVED

Similar questions